Deep response to a combination of mTOR inhibitor temsirolimus and dual immunotherapy of nivolumab/ipilimumab in poorly differentiated thyroid carcinoma with PTEN mutation: a case report and literature review - Oh, Youjin; Park, Joo Hee; Djunadi, Trie Arni; Shah, Zunairah; Chung, Liam Il-Young; Chae, Young Kwang (Frontiers in Endocrinology, 2024)
Treating advanced thyroid cancer presents challenges due to its resistance to various treatment modalities, thereby limiting therapeutic options. To our knowledge, this study is the first to report the efficacy of temsirolimus in conjunction with dual immunotherapy of nivolumab/ipilimumab to treat heavily treated advanced PDTC. A 50-year-old female initially presented with a rapidly enlarging mass on her right neck. Subsequent diagnosis revealed poorly differentiated thyroid carcinoma, leading to a total thyroidectomy followed by post-operative radioablation therapy. After four years, an examination for persistent cough revealed a recurrence of the disease within multiple mediastinal nodes. Genetic analysis of blood samples uncovered somatic mutations in the tumor, specifically involving PTEN and TP53. The disease progressed despite palliative radiation, lenvatinib, and nivolumab/ipilimumab therapy. Consequently, temsirolimus, functioning as an mTOR inhibitor, was introduced as an adjunct to the nivolumab/ipilimumab regimen. This combination approach yielded remarkable clinical improvement and disease control for a duration of approximately six months. Temsirolimus likely suppressed the aberrantly activated PI3K/AKT/mTOR signaling pathway, facilitated by the PTEN genetic alteration, thus engendering an effective treatment response. This synergy between targeted agents and immunotherapy presents a promising therapeutic strategy for advanced PDTC patients with limited treatment alternatives. In previous clinical trials, mTOR inhibitors have demonstrated the ability to maintain stable disease (SD) in 65% to 74% for advanced thyroid cancer patients, including those with PDTC. When combined with other targeted therapies, the observed SD or partial response rates range from 80% to 97%. Many of these trials primarily involved differentiated thyroid carcinoma, with diverse genetic mutations. Thyroid cancer patients with alterations in the PI3K/mTOR/Akt appeared to benefit most from mTOR inhibitors. However, no clear association between the efficacy of mTOR inhibitors and specific histologies or genetic mutations has been established. Future studies are warranted to elucidate these associations.